(untitled) (CAHIERS MAGELLANES-NS, 2024)
To find the best alternative, possessing dual activity as a food coloring and anti-diabetic agent, a red bacterial pigment was reported to show many promising potential therapeutic activities viz. anti-protozoan, antibacterial, antifungal, antiviral insecticidal, anti-parasitic, immune modulator, anticancer was studied for α-amylase inhibition potentials which play a key role in raising blood glucose levels. Both In silico and In vitro studies were performed. Advanced Auto dock software was used for docking studies taking prodigiosin, the red bacterial pigment, and the standard drug acarbose as ligands and pancreatic α-amylase as protein. Similarly, In vitro studies were also performed to substantiate the results of In silico studies. The test compounds prodigiosin and the standard drug acarbose exhibited binding energies of -7.1 Kcal mol-1, -7.6 Kcal mol-1 respectively against the protein 3BC9. In In vitro studies, the test compound exhibited strong α-amylase inhibition activity. Hence, we conclude that prodigiosin has potent human pancreatic alpha-amylase inhibitory activity, which may have an additional impact in the treatment of diabetes and as a food coloring agent.